Diálogos da Alma: uma outra história da loucura - Azevedo, Juliana Rocha de (2006)
The tesis intends to awake a new way of looking at madness. It presents as reference the Psychiatric Hospital Doctor João Machado (Natal/RN) and histories of life and narratives of four intern residents. The research in an ethical horizon, intends to give back to the subjects the voices long silented behind the institutions walls by their families and society in general. As well as to open the interpretations of science to receive and to dialogue with other itineraries of thought that, if on one hand does not restitute the explanation of the Real, on the other hand expresses other forms to see the world. Dislocated of the bigger social environment, the people identified as insane, construct their histories endowed with autonomy and displacements in relation to the social rules and structures that characterize our society, as much as in relation to the logical principles of thought that assume an objective and rational reality. As well as a remnants bedspread configured in a complex and unfinished object, the break up of histories of life of the interns, interviews with medical on psychiatrists to the Doctor João Machado Hospital, documents of the institution and depositions of that house, were the raw material to construct, with this tesis, another chapter of the 'history of madness'. In elapsing of the work innumerable voices have been heard. Some that study the phenomenon of madness, others that live this 'state of the being' in the world. We opt to detaching the first of an open conception on the theme through intellectuals as: João da Costa Machado, Ulysses Pernambucano, Nise da Silveira and Boris Cyrulnik. They express ethics compromised to the humanity of the being